Exploring Childrens' Experience in Using Edpuzzle: A Study to Explore Digital Tools - firdha hayati; Verawati (Tajdid Al-Athfal, 2022)
The use of technology or digital media during the Covid-19 pandemic as learning media for early childhood is essential. The lack of variation in digital media or technology used by teachers during online learning is the background for this research. The researcher sees the need for the development of interesting animated videos that can improve the development of children's language and art during pandemic. Edpuzzle is an animated video application that children and teachers can use to improve children's language and artistic development. Edpuzzle-based animated video was developed based on the results of needs analysis with animated videos created through PPT and modified using the voiceover feature. The theme chosen in this study is transportation with the sub-theme of buses, trains, and planes. The research subjects are 4 children aged 4-5 years. The data collection techniques used were observation checklists, questionnaires, interviews, and documentation which were analyzed quantitatively, descriptively and qualitatively. The results of all validation assessments are at average value of 4.1 with a very suitable category to be used. This media can also improve the language and art development ; that is, children acquire new vocabularies or language and express their art through free drawing, coloring and collaging